Voices from Chernobyl : the oral history of a nuclear disaster - Aleksievich, Svetlana, 1948-; Gessen, Keith (New York : Picador, 2006)
Voices From Chernobyl is the first book to present personal accounts of what happened on April 26, 1986, when the worst nuclear reactor accident in history contaminated as much as three quarters of Europe. Svetlana Alexievich--a journalist who now suffers from an immune deficiency developed while researching this book--interviewed hundreds of people affected by the meltdown. Their narratives form a crucial document revealing how the government masked the event with deception and denial. Harrowing and unforgettable, Voices From Chernobyl bears witness to a tragedy and its aftermath in a book that is as unforgettable as it is essential.
'First published in Russian as Tchernobylskaia Molitva by Editions Ostojie'--Title page verso.
Keywords: v; x; x